Effects of Single Nucleotide Polymorphisms in Human KCNMA1 on BK Current Properties - Plante, Amber E.; Lai, Michael H.; Lu, Jessica; Meredith, Andrea L. (Frontiers in Molecular Neuroscience, 2019)
BK Ca2+-activated K+ channels are important regulators of membrane excitability. Multiple regulatory mechanisms tailor BK current properties across tissues, such as alternative splicing, post-translational modifications, and auxiliary subunits. Another potential mechanism for modulating BK channel activity is genetic variation due to single nucleotide polymorphisms (SNPs). The gene encoding the human BK α subunit, KCNMA1, contains hundreds of SNPs. However, the variation in BK channel activity due to SNPs is not well-studied. Here, we screened the effects of four SNPs (A138V, C495G, N599D, R800W) on BK currents in HEK293T cells, selected based on predicted protein pathogenicity or disease linkage. We found that the SNPs C495G and R800W had the largest effects on BK currents, affecting the conductance-voltage relationship across multiple Ca2+ conditions in the context of two BK channel splice variants. In symmetrical K+, C495G shifted the V1/2 to more hyperpolarized potentials (by -15 to -20 mV) and accelerated activation, indicating C495G confers some gain-of-function properties. R800W shifted the V1/2 to more depolarized potentials (+15 to +35 mV) and slowed activation, conferring loss-of-function properties. Moreover, the C495G and R800W effects on current properties were found to persist with post-translational modifications. In contrast, A138V and N599D had smaller and more variable effects on current properties. Neither application of alkaline phosphatase to patches, which results in increased BK channel activity attributed to channel dephosphorylation, nor bi-directional redox modulations completely abrogated SNP effects on BK currents. Lastly, in physiological K+, C495G increased the amplitude of action potential-evoked BK currents, while R800W had a more limited effect. However, the introduction of R800W in parallel with the epilepsy-linked mutation D434G (D434G/R800W) decreased the amplitude of action potential-evoked BK currents compared to D434G alone. These results suggest that in a physiological context, C495G could increase BK activation, while the effects of the loss-of-function SNP R800W could oppose the gain-of-function effects of an epilepsy-linked mutation. Together these results implicate naturally occurring human genetic variation as a potential modifier of BK channel activity across a variety of conditions.